Spina Bifida Defying Folic Acid Supplementation - Raveenthiran V (EL-Med-Pub, 2012)
Pre-conceptional supplementation of folic acid is well known to reduce the incidence of spina bifida. But Athena is frequently perplexed to see this anomaly occurring despite folate supplementation. In a largest Canadian study, De Wal et al [1] screened 1.9 million live births to study the effect of mass fortification. On comparing pre and post fortification periods they noted only 46% reduction in the incidence of neural tube defects (NTD). What happens to the remaining 54%? Why do they defy "folic acid" logics? Recently several publications have shed more light on this intriguing question.